스마트 관광 진흥 및 활성화를 위한 지방자치단체 조례 분석 - 차재관(Jae Gwan Cha) (스마트미디어저널, 2024)
The purpose of this study is to examine the current status of ordinances enacted by local governments in relationship to the promotion and revitalization of smart tourism cities and to present the direction and improvements of ordinances to local governments through the content analysis of the ordinances. The ordinances of 15 local governments that have enacted and implemented smart tourism promotion ordinances as of June 2024 were analyzed by an analysis framework consisting of targets, promotion projects, delivery systems, and financial funding based on Gilbert and Terrell's policy analysis model. As a result of the analysis, it was found that the smart tourism promotion ordinances of local governments have recently been enacted and are in the attractive stage, focusing on technology, content, and service items applied to smart tourism rather than reflecting regional characteristics. As a result of analyzing the provisions related to the target, promoting projects, delivery systems, and financial funding in the composition of the ordinance, it was found that local governments were somewhat lacking in promoting smart tourism projects overall. Based on the analysis results, the direction of development of the smart tourism promotion ordinance was suggested. 본 연구는 스마트 관광 도시 진흥 및 활성화와 관련하여 지방자치단체가 시행 중인 조례 제정 현황을 살펴보고 조례의 내용분석을 통하여 지방자치단체에게 조례의 구축 방향과 개선점을 제시하는 데 목적이 있다. 이를 위하여 2024년 6월을 기준으로 스마트 관광 진흥 조례를 제정하여 시행하고 있는 15개 지방자치단체의 조례를 길버트(Gilbert)와 테렐(Terrell)의 정책분석 모형을 기반으로 대상, 진흥 사업, 전달 시스템, 재정 지원들로 구성된 분석틀에 의해 분석하였다. 본 연구 결과, 지방자치단체의 스마트 관광 진흥 조례는 최근에 제정되기 시작하여 유치기 단계에 있으며 지역 특성을 반영하기 보다는 스마트 관광에 적용되는 기술과 콘텐츠, 서비스 항목에 집중하는 것으로 나타났다. 조례의 내용 구성에 있어 대상, 지원사업, 전달 시스템, 재정 지원 관련 조항을 분석해 본 결과 전반적으로 스마트 관광사업을 추진에서 지방자치단체의 추진 의지가 다소 부족한 것으로 나타났다. 분석결과를 바탕으로 스마트 관광 진흥 조례의 발전 방향을 제시하였다.